Analisis Ekonomi Hijau Produk Domestik Regional Bruto (PDRB) Sub Sektor Pertanian Tanaman Pangan di Provinsi Kalimantan Selatan - Siti Wardah; Muhammad Anshar Nur (PPJP Universitas Lambung Mangkurat, 2023)
The main objectives of this study are the value of depletion, degradation, depreciation, and green GRDP of the food crop sub-sector in South Kalimantan Province. Data processing is done mathematically with green GRDP as the approach. Judging from the type of data, this research is a quantitative and descriptive study when viewed from the level of explanation. This study uses secondary data from the Central Statistics Agency (BPS) publications, the Department of Food Crops and Horticulture, South Kalimantan Province, and Bank Indonesia. The results showed that the value of Green GRDP in the Food Crops Sub-Sector in 2018 was Rp. 3.4 trillion, in 2019, it was Rp. 3.5 trillion, and in 2020, it was Rp. 3.7 trillion. The calculation results show that the value of the Green GRDP of the Food Crops Sub-Sector is smaller than the conventional GRDP because the depletion value of food plant resources and the value of soil degradation are quite high.